MiRNAs as potential therapeutic targets and biomarkers for non-traumatic intracerebral hemorrhage - Ilgiz Gareev; Ozal Beylerli; Boxian Zhao (BMC, 2024)
Abstract Non-traumatic intracerebral hemorrhage (ICH) is the most common type of hemorrhagic stroke, most often occurring between the ages of 45 and 60. Hypertension is most often the cause of ICH. Less often, atherosclerosis, blood diseases, inflammatory changes in cerebral vessels, intoxication, vitamin deficiencies, and other reasons cause hemorrhages. Cerebral hemorrhage can occur by diapedesis or as a result of a ruptured vessel. This very dangerous disease is difficult to treat, requires surgery and can lead to disability or death. MicroRNAs (miRNAs) are a class of non-coding RNAs (about 18-22 nucleotides) that are involved in a variety of biological processes including cell differentiation, proliferation, apoptosis, etc., through gene repression. A growing number of studies have demonstrated miRNAs deregulation in various cardiovascular diseases, including ICH. In addition, given that computed tomography (CT) and/or magnetic resonance imaging (MRI) are either not available or do not show clear signs of possible vessel rupture, accurate and reliable analysis of circulating miRNAs in biological fluids can help in early diagnosis for prevention of ICH and prognosis patient outcome after hemorrhage. In this review, we highlight the up-to-date findings on the deregulated miRNAs in ICH, and the potential use of miRNAs in clinical settings, such as therapeutic targets and non-invasive diagnostic/prognostic biomarker tools.